Exosomal microRNA-25 released from cancer cells targets SIK1 to promote hepatocellular carcinoma tumorigenesis. Issue 7 (July 2022) - Fu, Xiaoyu; Tang, Yujing; Wu, Wanfeng; Ouyang, Yi; Tan, Deming; Huang, Yan
Abstract: Background: Hepatocellular carcinoma (HCC) is recognized as a leading cause of cancer-associated fatality worldwide. Our study here aimed to probe the mechanism by which exosomes secreted by CSQT-2, an HCC cell line, affected the progression of HCC. Methods: Exosomes were extracted from CSQT-2 cells. Colony formation, Transwell, sphere formation and flow cytometric analyses were applied to assess cell biological activities. Microarray analysis detected the change of microRNA (miRNA) expression after exosome treatment, followed by RT-qPCR validation. Luciferase reporter was applied to detect the binding between SIK1 and miR-25. Xenograft studies in nude mice manifested tumor growth and metastatic ability of miR-25 and SIK1. Results: The exosome treatment enhanced cell malignant phenotype in vitro and tumor growth and liver and lung metastases in vivo . The exosomes elevated miR-25 expression in HCC cells. miR-25 targeted SIK1 which was decreased in the exosomes-treated cells. miR-25 inhibitor reduced cell malignant phenotype and attenuated tumorigenesis and metastasis in vivo . SIK1 silencing reversed the effect of miR-25 inhibitor. The exosome treatment potentiated the Wnt/β-catenin pathway in cells, whereas miR-25 inhibitor blunted the pathway activity. Conclusion: MiR-25 shuttled through CSQT-2-derived exosomes promoted the development of HCC by reducing SIK1 expression and potentiating the Wnt/β-catenin pathway.